Antibacterial Activity and Optimal Treatment of Ceftazidime-Avibactam and Aztreonam-Avibactam Against Bloodstream Infections Caused by Carbapenem-Resistant Klebsiella pneumoniae - Yu, Wei; Chen, Yunbo; Shen, Ping; Ji, Jinru; Ying, Chaoqun; Liu, Zhiying; Xiong, Luying; Qiu, Yunqing; Xiao, Yonghong (Frontiers in Pharmacology, 2021)
Objectives: This work was to investigate the activity and optimal treatments of ceftazidime-avibactam (CZA) and aztreonam-avibactam (AZA) against bloodstream infections caused by carbapenem resistant Klebsiella pneumoniae (BSIs-CRKP). Methods: A total of 318 nonduplicate BSIs-CRKP isolates were collected from Blood Bacterial Resistant Investigation Collaborative System (BRICS) program. The minimum inhibitory concentration (MIC) of CZA and AZA were determined by agar dilution method. Carbapenemase genes and multilocus sequence typing were amplified by PCR. Monte Carlo simulation (MCS) was conducted to calculate cumulative fraction of response (CFR) of different CZA or AZA administrations. Results: The MIC90 of CZA and AZA were 128/4 and 1/4 mg/L, respectively. There are 87.4 and 3.5% isolates carried blaKPC-2 and blaNDM-1. A total of 68 ST types were identified and 29 novel ST types. ST11 accounted for 66.6%. Further MCS showed CFR of CZA using two-step infusion therapy (rapid first-step 0.5 h infusion and slow second-step 3 h infusion, TSIT) (2.5 g 0.5 h, 3.75 g every 8 h with 3 h infusion and 3.75 g 0.5 h, 2.5 g every 8 h with 3 h infusion) was above 89%. The CFR of AZA with TSIT was above 96%. Conclusion: TSIT with sufficient pharmacokinetic conditions could be useful for enhancing the therapeutic efficacy of CZA and AZA against BSIs-CRKP.